2003
DOI: 10.1128/aem.69.8.4884-4891.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seasonal Environmental Variables on the Distribution of Presumptive Fecal Coliforms around an Antarctic Research Station

Abstract: Factors affecting fecal microorganism survival and distribution in the Antarctic marine environment include solar radiation, water salinity, temperature, sea ice conditions, and fecal input by humans and local wildlife populations. This study assessed the influence of these factors on the distribution of presumptive fecal coliforms around Rothera Point, Adelaide Island, Antarctic Peninsula during the austral summer and winter of February 1999 to September 1999. Each factor had a different degree of influence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 46 publications
1
47
0
3
Order By: Relevance
“…E. coli does not survive generally more than two or three weeks in low-nutrient environments in a viable and cultivable state (Neidhardt et al, 1996), and indications of its presence in nutrient-poor cave habitats should be carefully examined (Barton and Pace, 2005). Airborne fecal coliforms generally do not survive long outdoors, so the probability of causing infections for wildlife and humans is low (Hughes, 2003). Similar conclusion could be drawn for the underground environment.…”
Section: Airborne Microbessupporting
confidence: 67%
“…E. coli does not survive generally more than two or three weeks in low-nutrient environments in a viable and cultivable state (Neidhardt et al, 1996), and indications of its presence in nutrient-poor cave habitats should be carefully examined (Barton and Pace, 2005). Airborne fecal coliforms generally do not survive long outdoors, so the probability of causing infections for wildlife and humans is low (Hughes, 2003). Similar conclusion could be drawn for the underground environment.…”
Section: Airborne Microbessupporting
confidence: 67%
“…Lower solar irradiance had a reducing effect on the synthesis of Porphyra-334. In the Sfix treatment cells were exposed to high daily integrated PAR and UVAR irradiance, whereas the maximum UVBR irradiance and the daily UVBR dose were relatively low (around 20%) compared to natural spring conditions (Hernando 2011, Hughes 2003 (Table 1) in the Potter Cove area. Similar results were previously reported for a strain of Thalassiosira sp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial ecology, in contrast, has focused on defining and describing the diversity of taxa and classifying them into ecotypes (1,2). However, many studies have shown associations between particular bacterial communities and characteristics of the physical environment they are found in, for instance, soil (3,4) and freshwater (5) habitats, and of the seasonal dynamics of the bacterial community structure (6).…”
mentioning
confidence: 99%